Critical Discourse Analysis: Sensationalist Press in Close Cultural Contexts. Cases of Ajá (Perú) & La Cuarta (Chile) - Browne Sartori, Rodrigo (2011)
Social communication media are understood as relevant producers of images, prejudices and stereotypes that make up a vision and identity about speeches on difference. This article is part of a project on information science, and investigates how intercultural reality is carried out. In this case, this is applied to the local newspapers Ajá (Perú) and La Cuarta (Chile) which are highly read in both countries. At the same time, this study allows to observe how otherness and self image are perceived, and as a consequence, the development of intercultural journalism.